2014
DOI: 10.1111/jomf.12085
|View full text |Cite
|
Sign up to set email alerts
|

Marital Conflict in Older Couples: Positivity, Personality, and Health

Abstract: We examine the implications of health and personality characteristics for late-life marital conflict, using data from the 2010–11 wave of the National Social Life Health and Aging Project (NSHAP), a nationally representative study with data on both partners in 955 marital and cohabitational dyads. Using these data, we relate characteristics of husbands to characteristics of their wives, and vice versa. Wives with husbands in fair or poor physical health are more likely to report high levels of marital conflict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 76 publications
1
54
0
5
Order By: Relevance
“…"A gente vai discutir a novelinha todo dia, mas ela também pode discutir o futebolzinho de vez em quando, porque mulher não gosta entendeu, né" (H-3). Os resultados apresentados nessa categoria são apontados também na literatura como motivos de conflito (Faulkner et al, 2005;Giudici et al, 2011;Iveniuk, et al, 2014;Karahan, 2009;Pazo & Aguiar, 2012;Silva & Vandenberghe , 2009;Torossian et al, 2009). São problemas que os casais referem, normalmente, no início do casamento e que são resolvidos paulatinamente, enquanto outros surgem ao longo do ciclo vital.…”
Section: Eu Acho Que Também a Falta De Dinheiro àS Vezes O Desempreunclassified
See 2 more Smart Citations
“…"A gente vai discutir a novelinha todo dia, mas ela também pode discutir o futebolzinho de vez em quando, porque mulher não gosta entendeu, né" (H-3). Os resultados apresentados nessa categoria são apontados também na literatura como motivos de conflito (Faulkner et al, 2005;Giudici et al, 2011;Iveniuk, et al, 2014;Karahan, 2009;Pazo & Aguiar, 2012;Silva & Vandenberghe , 2009;Torossian et al, 2009). São problemas que os casais referem, normalmente, no início do casamento e que são resolvidos paulatinamente, enquanto outros surgem ao longo do ciclo vital.…”
Section: Eu Acho Que Também a Falta De Dinheiro àS Vezes O Desempreunclassified
“…Esses resultados corroboram outros estudos (Miller & Rempel, 2004;Sanford, 2006) quanto à expressão negativa das emoções que emergem das situações de conflito. As semelhanças e as diferenças encontradas quanto à canalização das emoções podem estar associadas às características individuais de cada participante, como autocontrole (Iveniuk et al, 2014;Pazo & Aguiar, 2012), ou apontar para a oscilação natural de emoções e de reações às quais as pessoas, especialmente nas relações amorosas, estão suscetíveis (Bolze et al, 2013).…”
Section: Eu Acho Que Também a Falta De Dinheiro àS Vezes O Desempreunclassified
See 1 more Smart Citation
“…The married tend to ignore problems with their spouses because the relationship is an important source of emotional closeness and intimacy (Luong, Charles, & Fingerman, 2011). Recent empirical research however suggests that in marriage, the husband's health has numerous effects on the wife's wellbeing while the wives' health does not have comparable effects on the husband's satisfaction with life (Iveniuk, Waite, Laumann, McClintock, & Tiedt, 2014), Researchers have identified a little relationship between education and life satisfaction. However, the relationship seems to disappear when income and occupation are statistically controlled.…”
Section: International Journal Of Social Science Researchmentioning
confidence: 99%
“…This can be defined as perceiving the same emotion in a partner as that which is perceived by outside observers" (p. 1). Iveniuk et al (2014) showed high neuroticism and low positivity of men are associated with more conflict among couples. Randall et al (2013) showed the association between marital cooperation and emotional coordination.…”
Section: Introductionmentioning
confidence: 99%